Examining the factors affecting saving in Asean / Roz Auzainee Rozman - Rozman, Roz Auzainee (2018)
Saving is balance of income that left after paying consumptions. All people know that we can't predict what will happen in future, that why we need to make a savings for emergencies or unexpected cases. Without set aside some money will make burdens in financial if any unexpected events is happen. It also can make improvement in economic growth and development for the country. Therefore, savings play an important role in every countries. The purpose for this paper is to measure the factors that affecting household saving rate in ASEAN (Malaysia, Thailand, Philippine and Singapore) in year 2007 to 2016. The dependent variable for this research is household saving rate and the independent variable which is interest rate, inflation rate and unemployment rate. The data collected from secondary data. Datastream is one of the secondary data that used in this research. This study was found that significant relationship between dependent and independent variable in ASEAN country.